2020
DOI: 10.2147/ott.s265853
|View full text |Cite
|
Sign up to set email alerts
|

<p>Identification of Long Non-Coding RNA <em>SNHG</em> Family as Promising Prognostic Biomarkers in Acute Myeloid Leukemia</p>

Abstract: Background: Small nucleolar RNA host gene (SNHG) family members are newly recognized lncRNAs, which have been revealed to be oncogenes in several cancers. However, little studies investigated the expression and clinical implications of SNHGs in AML. Methods: Herein, we systemically determined the prognostic role of the expression of SNHG family members in acute myeloid leukemia (AML). Results: Among the expression of all SNHG family members, we identified that only SNHG7 and SNHG12 expression were found to hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 18 publications
(25 reference statements)
0
19
0
Order By: Relevance
“…Six AS events regulated by SF3B4 in tumor samples overlapped with the top SF3B4 regulated AS events in ESCC. The oncogenic role of SRSF5 [ 49 ], PHF6 [ 50 ], SNHG12 [ 51 ] and KIAA1217 [ 52 ] have been reported in different tumors, but we firstly discovered that intron retention in these genes are repressed by SF3B4. Retained intron (RI) repression potentially leads to productive transcripts, because retained introns usually produce premature termination codons, which may generate unproductive, unstable transcripts or truncated proteins [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Six AS events regulated by SF3B4 in tumor samples overlapped with the top SF3B4 regulated AS events in ESCC. The oncogenic role of SRSF5 [ 49 ], PHF6 [ 50 ], SNHG12 [ 51 ] and KIAA1217 [ 52 ] have been reported in different tumors, but we firstly discovered that intron retention in these genes are repressed by SF3B4. Retained intron (RI) repression potentially leads to productive transcripts, because retained introns usually produce premature termination codons, which may generate unproductive, unstable transcripts or truncated proteins [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Non-coding RNAs (ncRNAs), such as long non-coding RNAs (lncRNAs) and microRNAs (miRNAs), have been confirmed to affect progression, growth and spread of cancers [6][7][8]. Among them, small nucleolar host gene 4 (SNHG4) is a novel lncRNA that belongs to SNHGs family, members of which have been documented to play critical roles in regulating tumorigenesis [9][10][11]. Recent studies have identified that SNHG4 functions as an important carcinogenic molecule in several cancers.…”
mentioning
confidence: 99%
“…Six AS events regulated by SF3B4 in tumor samples overlapped with the top SF3B4 regulated AS events in ESCC. The oncogenic role of SRSF5 [49], PHF6 [50], SNHG12 [51] and KIAA1217 [52] have been reported in different tumors, but we rstly discovered that intron retention in these genes are repressed by SF3B4. Retained intron (RI) repression potentially leads to productive transcripts, because retained introns usually produce premature termination codons, which may generate unproductive, unstable transcripts or truncated proteins [53].…”
Section: Discussionmentioning
confidence: 94%